DIFFICULTY ANALYSIS OF STUDENTS OF CLASS X SMAN 3 SUNGAI PENUH IN SOLVING PHYSICS PROBLEMS IN THE FORM OF GRAPHIC IN STRAIGHT MOTION MATERIAL - Korry Nilyani; - Ratnawulan; - Gusnedi; Renol Afrizon (Universitas Negeri Padang, 2022)
This study aims to determine the difficulties of students in solving physics problems in the form of graphs and profiles of students' difficulties in the material of straight motion. This research method is qualitative research. The population in this study were students of class X Science at the state senior high school 3 Sungai Penuh who had studied the material of straight motion. The sampling technique used is Simple Random Sampling, from this technique one trial class was selected, namely X Science 2 and one class as a sample, namely class X Science 1. The data collection method was diagnostic tests and was supported by interview results. The analysis was carried out using descriptive percentages.The results show that students' ability to solve physical problems with graphs has a low percentage of interpretation ability of 40.61%; interpolation ability of 30.6%; extrapolation ability of 30.46%; and the ability to transform by 39.65%. The student difficulty profile in this study based on the minimum criteria of mastery learning was still having difficulty for all indicators with an average of weak categories. The student's difficulty profile on the material profile is still having difficulties for all sub-materials with an average of weak categories. In the difficulty profile based on prerequisite knowledge, the proportion of students who have difficulty in determining the area of flat shapes is 51.72% including the medium category, the percentage of students' difficulty in arithmetic operations is 66.05% including the high category, the proportion of students' difficulties in linear equations is 72.41% included in the high category.